Solid electrolytic capacitor
By eliminating the intermediate layer and optimizing the hardness of the carbon and metal layers in solid electrolytic capacitors, the design addresses issues of volume efficiency and bonding strength, resulting in a more reliable and efficient capacitor.
Patent Information
- Application Number
- JP2023145024
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-19
AI Technical Summary
Existing solid electrolytic capacitors with intermediate layers between the carbon paste and metal layers face issues of increased thickness, reduced volume efficiency, and insufficient bonding strength, affecting reliability.
The solid electrolytic capacitor design eliminates the intermediate layer by forming a carbon layer and a metal layer with specific hardness profiles, where one layer is relatively soft and the other is hard, enhancing adhesion and reducing stress during the sealing process.
This configuration improves bonding strength, suppresses ESR changes during high-temperature tests, and enhances volume efficiency by reducing the overall thickness of the capacitor, thereby increasing reliability and performance.
Smart Images

Figure 2025038408000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid electrolytic capacitor including a conductive polymer layer, a carbon paste layer, and a metal layer. [Background technology]
[0002] Conventionally, various configurations of solid electrolytic capacitors having a conductive polymer layer, a carbon paste layer, and a metal layer have been known. The carbon paste layer is composed of carbon particles and resin. The metal layer is composed of metal particles and resin. In such configurations, various structures have been studied to improve the connection strength between the carbon paste layer and the metal layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2005-86125 A Summary of the Invention [Problem to be solved by the invention]
[0004] The solid electrolytic capacitor of Patent Document 1 has the following configuration.
[0005] The binder of the carbon paste layer is made of thermosetting resin. The metal layer is made of a silver paste layer whose main components are silver particles and resin. An intermediate layer is provided between the carbon paste layer and the metal layer. The intermediate layer is made of metal particles, carbon particles or a mixture of these conductive particles, with a fluorine-based plastomer used as a binder.
[0006] Patent Document 1 discloses a structure in which an intermediate layer is provided between a carbon paste layer and a metal layer in order to relieve stress during exposure to high temperatures and suppress an increase in ESR.
[0007] However, since the solid electrolytic capacitor described in Patent Document 1 has an intermediate layer, the thickness of the entire capacitor is increased. In other words, there is a risk that the volumetric efficiency for the capacitance is reduced. In addition, the configuration of Patent Document 1 has a problem that affects reliability, such as insufficient bonding strength between the carbon paste layer and the metal layer.
[0008] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a solid electrolytic capacitor which has improved volumetric efficiency and bonding strength and is highly reliable. [Means for solving the problem]
[0009] The solid electrolytic capacitor of the present invention includes a capacitor element, a sealing body, a first external electrode, and a second external electrode. The capacitor element includes a flat membrane-like main body including a valve metal and having a porous layer with a plurality of holes on the surface of the valve metal, a dielectric layer formed on a cathode-forming region, and a solid electrolyte layer formed on the dielectric layer. The capacitor element further includes an anode terminal region in which the solid electrolyte layer is not formed on the main body, and a cathode-forming region in which the solid electrolyte layer is formed. A carbon layer is formed so as to cover the solid electrolyte layer formed in the cathode-forming region, and a metal layer is formed so as to cover the carbon layer.
[0010] The sealing body seals a laminate in which a plurality of capacitor elements are stacked with an insulating resin. The first external electrode is connected to an end of the anode terminal region. The second external electrode is connected to the cathode formation region.
[0011] In this solid electrolytic capacitor, the indentation hardness of the carbon layer and the metal layer is measured by a nanoindentation method. When the first indentation hardness of the carbon layer and the second indentation hardness of the metal layer are measured, one of the first indentation hardness and the second indentation hardness is 0.15 GPa or less, and the other is 0.20 GPa or more.
[0012] In this structure, either the carbon layer or the metal layer is relatively soft, while the other is relatively hard. That is, during heating and pressurization, the harder layer of either the carbon layer or the metal layer bites into the other soft layer. This improves the adhesion between the carbon layer and the metal layer. That is, during high-temperature reliability testing, the ESR change of the solid electrolytic capacitor is suppressed.
[0013] Furthermore, this configuration does not require a layer for connecting the carbon layer and the metal layer, which allows the solid electrolytic capacitor to be made smaller, thereby improving volumetric efficiency.
[0014] In addition, the presence of the soft layer reduces stress during the sealing process, which reduces the stress on the dielectric layer (dielectric coating) during the sealing process, thereby reducing damage to the dielectric layer. In other words, the leakage current can be reduced. Effect of the Invention
[0015] According to the present invention, it is possible to provide a solid electrolytic capacitor which has improved volumetric efficiency and bonding strength and is highly reliable. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a side cross-sectional view of the solid electrolytic capacitor according to the first embodiment. [Diagram 2] FIG. 2(A) is an enlarged view of a portion of the capacitor element according to the first embodiment, and FIG. 2(B) is a side cross-sectional view of the capacitor element. [Diagram 3] FIG. 3(A) is an image diagram showing an enlarged view of a portion of the carbon layer and metal layer according to the first embodiment, and FIG. 3(B) is an enlarged view of a portion of the carbon layer and metal layer to which a conventional configuration is applied. [Figure 4] FIG. 4 is a flowchart showing a procedure for forming the solid electrolytic capacitor according to the first embodiment. [Diagram 5]FIG. 5 is an enlarged conceptual diagram showing a part of the carbon layer and the metal layer according to the second embodiment. [Figure 6] FIG. 6 is a flowchart showing a procedure for forming the solid electrolytic capacitor according to the second embodiment. [Figure 7] FIG. 7 is a table comparing the LC yield rate and ESR change rate between solid electrolytic capacitors and a conventional configuration. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] [First embodiment] A solid electrolytic capacitor 1 according to a first embodiment of the present invention will be described with reference to the drawings. Fig. 1 is a side cross-sectional view of the solid electrolytic capacitor according to the first embodiment.
[0018] (Structure of solid electrolytic capacitor) The solid electrolytic capacitor 1 includes a capacitor assembly 10, a first external electrode 20, a second external electrode 30, and an insulating resin body 40.
[0019] The capacitor assembly 10 includes a plurality of capacitor elements 11 and a conductive member 19. The conductive member 19 is preferably an electrode paste containing, for example, nickel, silver, or copper as a main component. The maximum thickness of the conductive member 19 is preferably 2 μm or more and 20 μm or less. Note that, if a conductivity equal to or higher than a desired conductivity can be obtained between the plurality of capacitor elements 11 without using the conductive member 19, it is possible to omit the conductive member 19.
[0020] In this embodiment, the number of capacitor elements 11 constituting capacitor assembly 10 is not limited as long as it is plural. The structure of capacitor element 11 will be described in detail later.
[0021] The plurality of capacitor elements 11 are stacked. A capacitor assembly 10 (laminate) is formed by stacking the plurality of capacitor elements 11. At this time, the plurality of capacitor elements 11 are formed so as to be approximately parallel to each other.
[0022] The capacitor assembly 10 is sealed with an insulating resin body 40. This forms a sealing body 400. The sealing body 400 has a generally rectangular parallelepiped shape having a top surface 401, a bottom surface 402, a first surface 403, and a second surface 404. As described below, the surface on which the first external electrode 20 is formed by extending from the first surface 403 and the surface on which the second external electrode 30 is formed by extending from the second surface 404 are referred to as the bottom surface 402 for the sake of convenience, and the surface facing away from the bottom surface 402 is referred to as the top surface 401.
[0023] At this time, some of the multiple capacitor elements 11 are exposed from first surface 403 of sealing body 400. The surface (first surface 403) where the multiple capacitor elements 11 are linearly exposed from insulating resin body 40 is connected to first external electrode 20.
[0024] The first external electrode 20 is formed along the sealing body 400. Specifically, the first external electrode 20 is disposed across the first surface 403 and the bottom surface 402.
[0025] The first external electrode 20 is, for example, a Cu alloy (copper alloy)-based material or an iron alloy-based material. The first external electrode 20 is formed of, for example, a material cut out from a metal plate.
[0026] The first external electrode 20 is preferably made of a metal material that is easy to bend and has high conductivity. In this case, the first external electrode 20 is preferably arranged so as to be bent along the first surface 403 and the bottom surface 402 of the sealing body 400.
[0027] The second external electrode 30 is formed along the sealing body 400. Specifically, the second external electrode 30 is disposed across the second surface 404 and the bottom surface 402. The capacitor element 11 and the second external electrode are joined by a conductive adhesive 50 made of silver paste or the like.
[0028] The connection layers (conductive layers including solid electrolyte layer 113) of the multiple capacitor elements 11 are electrically and physically connected to second external electrode 30 by conductive adhesive 50.
[0029] The second external electrode 30 is preferably formed of a metal material that is easy to bend and has high conductivity, such as a Cu alloy (copper alloy) material or an iron alloy material. The second external electrode 30 is formed of a material cut out from a metal plate, for example. The first external electrode 20 and the second external electrode 30 may be made of the same material or different materials.
[0030] The insulating resin body 40 is mainly made of resin and may contain a filler. As the resin, for example, epoxy resin, phenol resin, polyimide resin, silicone resin, polyamide resin, liquid crystal polymer, etc. are preferable. The resin may be in the form of either solid resin or liquid resin. It is preferable that the corners are rounded by barrel polishing after the resin sealing. As the filler, for example, silica particles, alumina particles, etc. are preferable. The maximum diameter of the filler is preferably, for example, 30 μm or more and 40 μm or less. It is more preferable that the material contains silica particles in solid epoxy resin and phenol resin.
[0031] (Capacitor element structure) The structure of capacitor element 11 will be described in more detail with reference to FIGS. 2(A) and 2(B).
[0032] Fig. 2(A) is a diagram showing an enlarged portion of the capacitor element according to the first embodiment, and Fig. 2(B) is a side cross-sectional view of the capacitor element. Fig. 3(A) is an image showing an enlarged portion of the carbon layer and metal layer according to the first embodiment. Fig. 3(B) is an enlarged portion of the carbon layer and metal layer to which a conventional configuration is applied, as a comparison with Fig. 3(A).
[0033] Capacitor element 11 includes electrode foil 111, dielectric layer 112, solid electrolyte layer 113, carbon layer 114, and metal layer 115. Electrode foil 111 includes electrode layer 111F and porous layer 111L.
[0034] A more specific structure of the electrode foil 111 is as follows. The electrode layer 111F is made of, for example, a simple metal such as aluminum, tantalum, niobium, titanium, zirconium, magnesium, silicon, or an alloy containing these metals. The electrode layer 111F is preferably made of aluminum or an aluminum alloy. A porous layer 111L is formed on the surface layer portion of the electrode layer 111F. The porous layer 111L is formed by etching the surface of the electrode layer 111F. This makes the porous layer 111L a porous body. The electrode foil 111 may be a valve action metal that exhibits so-called valve action.
[0035] The electrode foil 111 is provided with a dielectric layer 112. As shown in FIG. 2(A) and FIG. 2(B), the electrode foil 111 has a first surface F1 and a second surface F2 that face each other in the Z-axis direction. The electrode foil 111 further includes a third surface F3, a fourth surface F4, a fifth surface F5, and a sixth surface F6 that are connected to the first surface F1 and the second surface F2 and are parallel to the Z-axis direction. The third surface F3 and the fourth surface F4 are parallel to the Y-axis direction. The fifth surface F5 and the sixth surface F6 are parallel to the X-axis. The dielectric layer 112 covers the first surface F1, the second surface F2, the fourth surface F4, the fifth surface F5, and the sixth surface F6 of the electrode foil 111.
[0036] The dielectric layer 112 is preferably made of an oxide film of the electrode foil 111 (porous layer 111L). When an aluminum foil is used for the electrode layer 111F, the dielectric layer 112 is formed by applying a voltage in an aqueous solution containing boric acid, phosphoric acid, adipic acid, or a sodium salt or ammonium salt thereof, and anodizing the same. The thickness of the dielectric layer 112 is preferably 10 nm or more and 100 nm or less.
[0037] Solid electrolyte layer 113 covers the outer surface of dielectric layer 112 (at least the surface opposite to the surface in contact with electrode foil 111). Solid electrolyte layer 113 is also filled in a large number of pores covered with dielectric layer 112.
[0038] More specifically, the solid electrolyte layer 113 includes, for example, an inner layer and an outer layer.
[0039] The inner layer is a layer on the dielectric layer 112 side of the solid electrolyte layer 113, and may be, for example, a PEDOT:PSS layer realized by a conductive polymer having a skeleton of pyrroles, thiophenes, anilines, or the like, or a conductive polymer having a skeleton of thiophenes, such as PEDOT [poly(3,4-ethylenedioxythiophene)], and complexed with polystyrene sulfonic acid (PSS) as a dopant. The inner layer is formed by a method of forming a polymer film of poly(3,4-ethylenedioxythiophene) or the like on the surface of the dielectric layer 112 using an electrolyte solution serving as a base for forming the solid electrolyte layer 113, for example, a treatment liquid containing a monomer such as 3,4-ethylenedioxythiophene, or a method of applying a dispersion of a polymer such as poly(3,4-ethylenedioxythiophene) to the surface of the dielectric part and drying it, or the like.
[0040] The outer layer is a layer formed on the outside of the inner layer. For example, the outer layer is a layer formed so as to cover the entire surface of the inner layer after the inner layer is formed to fill the fine recesses of the porous portion. The thickness of the outer layer is preferably 2 μm or more and 20 μm or less. The outer layer is formed by a method of forming a polymer film of poly(3,4-ethylenedioxythiophene) or the like on the surface of the inner layer using an electrolyte solution that is the base for forming the solid electrolyte layer 113, for example, a treatment liquid containing a monomer such as 3,4-ethylenedioxythiophene, or a method of applying a dispersion or paste of a polymer such as poly(3,4-ethylenedioxythiophene) to the surface of the inner layer portion and drying it, or the like.
[0041] The carbon layer 114 is formed so as to cover the outer layer (solid electrolyte layer 113). The carbon layer 114 is formed, for example, by applying a conductive paste in which an insulating resin such as a phenolic resin is mixed with carbon or graphene particles. In this embodiment, the carbon layer 114 is formed using a conductive paste in which a phenolic resin and carbon particles are mixed.
[0042] The metal layer 115 is formed so as to cover the carbon layer 114. The metal layer 115 is formed, for example, by applying a silver paste containing silver particles and polypropylene resin. In this embodiment, the metal layer 115 is formed using a silver paste in which polypropylene resin and silver particles are mixed. The structures of the carbon layer 114 and the metal layer 115 will be described in more detail later.
[0043] With this configuration, capacitor element 11 becomes a flat-film solid electrolytic capacitor. In this capacitor element 11, electrode foil 111 corresponds to the anode, and metal layer 115 corresponds to the cathode. The region of electrode foil 111 where solid electrolyte layer 113, carbon layer 114, and metal layer 115 are not formed corresponds to the "anode terminal region" of the present invention, and the region where solid electrolyte layer 113, carbon layer 114, and metal layer 115 are formed corresponds to the "cathode formation region" of the present invention. Electrode foil 111 corresponds to the "main body" of the present invention.
[0044] (Specific structure of carbon layer and metal layer) Next, the structures of the carbon layer 114 and the metal layer 115 will be described in more detail with reference to FIG. 3(A) and FIG. 3(B).
[0045] First, the hardness of the carbon layer 114 and the metal layer 115 will be defined. The hardness of the carbon layer 114 (first indentation hardness) and the hardness of the metal layer 115 (second indentation hardness) are measured, for example, by using the nanoindentation method defined by ISO14577. By using the nanoindentation method, the hardness of the carbon layer 114 and the metal layer 115 is calculated as a numerical value. More specifically, a Berkovich indenter is pressed into the first surface F1 or the second surface F2 of the carbon layer 114 and the metal layer 115. The depth and area of the depression formed by the pressing of the Berkovich indenter, or the load when a depression of a certain depth is formed, etc. are measured. The hardness of the carbon layer 114 and the metal layer 115 is calculated using the measurement results. Here, when the hardness (first indentation hardness) of the carbon layer 114 is measured, it is preferable to perform the measurement before the metal layer 115 is formed. Furthermore, it is preferable to measure the hardness (second indentation hardness) of metal layer 115 before it is laminated with capacitor element 11. Alternatively, it is also possible to form a coating film similar to carbon layer 114 and metal layer 115 on a glass substrate or the like using a paste for forming carbon layer 114 and metal layer 115, and then heat-harden the coating to measure the hardness by pressing a Berkovich indenter into the coating.
[0046] The first indentation hardness of the carbon layer 114 in this embodiment, calculated using the above-mentioned nanoindentation method, was 0.50 GPa, and the second indentation hardness of the metal layer 115 was 0.08 GPa. In other words, since the first indentation hardness is greater than the second indentation hardness, the carbon layer 114 is harder than the metal layer 115. The first indentation hardness and the second indentation hardness are values measured after pressurization and heating.
[0047] In the present invention, the definition of "after heating and pressing" includes a state in which solid electrolytic capacitor 1 is heated and pressed under the same conditions as those for heating and pressing solid electrolytic capacitor 1. More specifically, it also includes a case in which capacitor element 11 with carbon layer 114 formed but not metal layer 115 formed is heated and pressed, and a case in which capacitor element 11 with carbon layer 114 and metal layer 115 formed is heated and pressed.
[0048] In this way, the solid electrolytic capacitor 1 is formed by stacking the capacitor elements 11, each having the carbon layer 114 and the metal layer 115 with different hardness, and applying heat and pressure (details will be described later). At this time, as shown in FIG. 3(A), the hard carbon layer 114 bites into the soft metal layer 115. More specifically, the carbon layer 114 bites into the metal layer 115 beyond the surface (boundary surface BD) where the carbon layer 114 and the metal layer 115 abut. This improves the adhesion between the carbon layer 114 and the metal layer 115. In other words, the change in ESR during the high-temperature reliability test is suppressed.
[0049] Here, the conventional configuration using Fig. 3(B) is compared with the structure in Fig. 3(A). In Fig. 3(B), the hardness of carbon layer 1141 and metal layer 1151 are approximately the same. In this case, when a solid electrolytic capacitor is formed under the same conditions as the configuration in Fig. 3(A), carbon layer 114 and metal layer 115 are bonded without crossing boundary surface BD. Note that the configuration in which boundary surface BD is not crossed includes a state in which boundary surface BD is not crossed due to thermal stress or manufacturing error when forming the solid electrolytic capacitor. A comparison of specific numerical values with the conventional configuration will be described later.
[0050] Thus, when comparing the configuration of Fig. 3(A) with the conventional configuration of Fig. 3(B), the adhesion between the carbon layer 114 and the metal layer 115 in the solid electrolytic capacitor 1 of Fig. 3(A) is higher than that in the conventional configuration. Furthermore, by providing the soft metal layer 115, the stress in the sealing process is alleviated. Therefore, damage to the dielectric layer can be reduced, and leakage current can be reduced.
[0051] In the above example, a Berkovich indenter is used in the measurement using the nanoindentation method. However, depending on the configuration of the carbon layer 114 and the metal layer 115, an appropriate indenter may be used from among Vickers, cube corner, cone, sphere, flat punch, etc.
[0052] (Method of manufacturing solid electrolytic capacitor) The solid electrolytic capacitor 1 having the above-mentioned configuration is manufactured, for example, as follows: Fig. 4 is a flow chart showing an example of a schematic flow of the method for manufacturing the solid electrolytic capacitor according to this embodiment.
[0053] Capacitor element 11 is formed. Specifically, as shown in Figures 2(A) and 2(B), dielectric layer 112 and solid electrolyte layer 113 are formed on a plurality of electrode foils 111 (S11).
[0054] Next, as shown in FIGS. 2(A) and 2(B), a carbon layer 114 is formed so as to cover the solid electrolyte layer 113 (S12).
[0055] 2(A) and 2(B), metal layer 115 is formed so as to cover carbon layer 114 (S13). At this time, metal layer 115 is softer than carbon layer 114. In other words, carbon layer 114 is harder than metal layer 115. The hardness of carbon layer 114 and metal layer 115 are adjusted by the composition of the resin contained in each layer, the heat properties, etc.
[0056] 1, capacitor elements 11 are stacked to form capacitor assembly 10 (S14). When forming capacitor assembly 10, the stacked capacitor elements 11 are heated and pressurized. As described above, if carbon layer 114 is a thermosetting resin and metal layer 115 is a thermoplastic resin, as the reaction due to heating and pressurization progresses, carbon layer 114 becomes harder and metal layer 115 becomes softer. This causes carbon layer 114 to bite into metal layer 115.
[0057] Next, as shown in FIG. 1, the capacitor assembly 10 is sealed with an insulating resin body 40 (S15).
[0058] Next, sealing body 400 is ground to expose electrode foil 111. In the anode formation region of capacitor assembly 10, first external electrode 20 is formed on the end face (first surface 403) of the anode region of capacitor assembly 10 (S16).
[0059] Next, as shown in FIG. 1, in the cathode formation region of the capacitor assembly 10, the end face (second surface 404) of the cathode region of the capacitor assembly 10 is joined to the second external electrode 30 using a conductive adhesive 50 such as silver paste (S17).
[0060] Next, the first external electrode 20 is bent along the first surface 403 and the bottom surface 402 of the sealing body 400. More specifically, the first external electrode 20 is bent along the bottom surface 402 of the sealing body 400. Similarly, the second external electrode 30 is bent along the second surface 404 and the bottom surface 402 of the sealing body 400 (S18).
[0061] In the above-described configuration, the lead frame (a configuration in which the terminal is drawn out to the outside by a conductive plate material) is formed after forming the sealing body 400. However, the sealing body 400 may be formed after forming the first external electrode 20 in step S16 and the second external electrode 30 in step S17.
[0062] In this manner, in the heating and pressurizing process for forming capacitor assembly 10 in step S14, carbon layer 114 bites into metal layer 115. This improves the adhesion between carbon layer 114 and metal layer 115. In other words, the change in ESR during high-temperature reliability testing is suppressed.
[0063] Furthermore, by providing the soft metal layer 115, the stress in the sealing process of step S15 is alleviated, so that damage to the dielectric layer can be reduced, and leakage current can be reduced.
[0064] [Second embodiment] A solid electrolytic capacitor 1A according to a second embodiment of the present invention will be described with reference to the drawings. Fig. 5 is an image showing an enlarged view of a part of a carbon layer and a metal layer according to the second embodiment. Fig. 6 is a flow chart showing a procedure for forming the solid electrolytic capacitor according to the second embodiment.
[0065] 5, the solid electrolytic capacitor 1A according to the second embodiment is different from the solid electrolytic capacitor 1 according to the first embodiment in the relationship in hardness between the carbon layer 114A and the metal layer 115A. More specifically, the metal layer 115A is relatively harder than the carbon layer 114A. The other configurations of the solid electrolytic capacitor according to the second embodiment are similar to those of the solid electrolytic capacitor according to the first embodiment, and a description of similar parts will be omitted.
[0066] The carbon layer 114A is formed, for example, by applying a conductive paste in which a thermoplastic insulating resin such as polyester resin is mixed with carbon or graphene particles. In this embodiment, a conductive paste in which polyester resin and carbon particles are mixed is used to form the carbon layer 114A. The metal layer 115A is formed, for example, by applying a silver paste containing silver particles and a thermosetting insulating resin such as phenolic resin. In this embodiment, a silver paste in which phenolic resin and silver particles are mixed is used to form the metal layer 115A.
[0067] When measured using the nanoindentation method in the same manner as in the first embodiment, the first indentation hardness of the carbon layer 114A in this embodiment was 0.09 GPa, and the second indentation hardness of the metal layer 115A was 0.40 GPa. The hardnesses were measured after applying pressure and heat. That is, since the second indentation hardness is greater than the first indentation hardness, the metal layer 115A is harder than the carbon layer 114A. In other words, the carbon layer 114A is softer than the metal layer 115A.
[0068] That is, as shown in Fig. 5, the metal layer 115A bites into the carbon layer 114A. More specifically, the metal layer 115A bites into the carbon layer 114A beyond the surface (boundary surface BD) where the carbon layer 114A and the metal layer 115A contact each other. This improves the adhesion between the carbon layer 114A and the metal layer 115A. That is, the change in ESR during the high-temperature reliability test is suppressed.
[0069] 6, when forming the solid electrolytic capacitor 1A, the configuration of step S21 is different. More specifically, it is as follows.
[0070] As shown in FIGS. 2(A) and 2(B), a carbon layer 114A is formed so as to cover the solid electrolyte layer 113 (S12).
[0071] 2(A) and 2(B), a metal layer 115A is formed so as to cover the carbon layer 114A (S21). At this time, the metal layer 115A is harder than the carbon layer 114A.
[0072] 1, capacitor elements 11 are stacked to form capacitor assembly 10 (S14). When forming capacitor assembly 10, stacked capacitor elements 11 are heated and pressurized.
[0073] Even with this configuration, the metal layer 115A bites into the carbon layer 114A as shown in Fig. 5. More specifically, the metal layer 115A bites into the carbon layer 114A beyond the surface (boundary surface BD) where the carbon layer 114A and the metal layer 115A contact each other. This improves the adhesion between the carbon layer 114A and the metal layer 115A. In other words, the change in ESR during high-temperature reliability testing is suppressed.
[0074] Furthermore, by providing the soft carbon layer 114A, the stress in the sealing process of step S14 is alleviated, so that damage to the dielectric layer can be reduced, and leakage current can be reduced.
[0075] [Comparison of specific numerical examples] Next, a comparison will be made between the solid electrolytic capacitor formed using the above-mentioned configuration and a solid electrolytic capacitor with a conventional configuration using specific numerical examples. Figure 7 is a table comparing the LC yield rate and ESR change rate of the solid electrolytic capacitor with the conventional configuration.
[0076] The configurations of the solid electrolytic capacitors according to the first and second embodiments are compared with those of Comparative Example 1 and Comparative Example 2.
[0077] (Configuration of Comparative Example 1) The configuration of Comparative Example 1 is as follows. The carbon layer is formed by applying a conductive paste that is a mixture of polyester resin and carbon particles. The metal layer is a silver paste containing silver particles and polypropylene resin.
[0078] Other than the above configuration, Comparative Example 1 is similar to the configuration of the first embodiment. At this time, the first indentation hardness of the carbon layer measured by the nanoindentation method is 0.09 GPa, and the second indentation hardness of the metal layer is 0.08 GPa.
[0079] (Configuration of Comparative Example 2) The configuration of Comparative Example 2 is as follows. The carbon layer is formed by applying a conductive paste in which phenolic resin and carbon particles are mixed. The metal layer is a silver paste containing silver particles and phenolic resin. Other than the above configuration, Comparative Example 2 is similar to the configuration of the first or second embodiment. The first indentation hardness of the carbon layer measured by nanoindentation method is 0.50 GPa, and the second indentation hardness of the metal layer measured by nanoindentation method is 0.40 GPa.
[0080] 7 shows the results of comparing the solid electrolytic capacitors formed under the conditions of the first embodiment, the second embodiment, Comparative Example 1, and Comparative Example 2. The LC yield rate is calculated by measuring the leakage current (LC) of the solid electrolytic capacitor and using the percentage of solid electrolytic capacitors whose leakage current is equal to or less than a certain reference value. In addition, a high-temperature load test was performed on the completed solid electrolytic capacitor in a temperature environment of 125°C, in which a rated voltage was applied for 1000 hours. The ESR change rate was calculated from the rate of change in the equivalent series resistance (ESR) measurement value before and after the high-temperature load test.
[0081] Examples 1, 3, and 5 are configurations of the solid electrolytic capacitor according to the first embodiment. Examples 1, 3, and 5 have different parameters as shown below. In the solid electrolytic capacitors according to Examples 1, 3, and 5, one of the first indentation hardness of the carbon layer 114 and the second indentation hardness of the metal layer 115 is 0.15 GPa or less, and the other is 0.20 GPa or more.
[0082] More specifically, it is as follows. In Example 1, the first indentation hardness of the carbon layer 114 is 0.50 GPa, which is equal to or greater than 0.20 GPa. The second indentation hardness of the metal layer 115 is 0.08 GPa, which is equal to or less than 0.15 GPa. In Example 1, the LC yield rate was 97%, and the ESR change rate was 1.1 times.
[0083] In Example 3, the first indentation hardness of the carbon layer 114 is 0.30 GPa, which is equal to or greater than 0.20 GPa. The second indentation hardness of the metal layer 115 is 0.10 GPa, which is equal to or less than 0.15 GPa. In Example 3, the LC yield rate was 96%, and the ESR change rate was 1.2 times.
[0084] In Example 5, the first indentation hardness of the carbon layer 114 is 0.20 GPa or more, and the second indentation hardness of the metal layer 115 is 0.15 GPa or less. In Example 5, the LC yield rate was 95%, and the ESR change rate was 1.3 times.
[0085] Examples 2, 4, and 6 are configurations of the solid electrolytic capacitor according to the second embodiment. In Examples 2, 4, and 6, the parameters are changed as shown below. In the solid electrolytic capacitor according to the second embodiment, one of the first indentation hardness of the carbon layer 114A and the second indentation hardness of the metal layer 115A is 0.15 GPa or less, and the other is 0.20 GPa or more.
[0086] More specifically, the results are as follows. In Example 2, the first indentation hardness of the carbon layer 114A is 0.09 GPa, which is a value not greater than 0.15 GPa. The second indentation hardness of the metal layer 115A is 0.40 GPa, which is a value not less than 0.20 GPa. In Example 2, the LC yield rate was 97%, and the ESR change rate was 1.2 times.
[0087] In Example 4, the first indentation hardness of the carbon layer 114A was 0.10 GPa, which was a value not greater than 0.15 GPa. The second indentation hardness of the metal layer 115A was 0.30 GPa, which was a value not less than 0.20 GPa. In Example 4, the LC yield rate was 96%, and the ESR change rate was 1.3 times.
[0088] In Example 6, the first indentation hardness of the carbon layer 114A is 0.15 GPa, which is a value of 0.15 GPa or less, and the second indentation hardness of the metal layer 115A is 0.20 GPa, which is a value of 0.20 GPa or more. In Example 6, the LC yield rate was 95%, and the ESR change rate was 1.4 times.
[0089] In the solid electrolytic capacitor of Comparative Example 1, the first indentation hardness of the carbon layer is 0.09 GPa, and the second indentation hardness of the metal layer is 0.08 GPa. That is, the condition that both the first indentation hardness of the carbon layer and the second indentation hardness of the metal layer are 0.15 GPa or less is satisfied. However, the condition that both the first indentation hardness of the carbon layer and the second indentation hardness of the metal layer are 0.20 GPa or more is not satisfied. In Comparative Example 1, the LC yield rate was 98%, and the ESR change rate was 2.2 times.
[0090] In the solid electrolytic capacitor of Comparative Example 2, the first indentation hardness of the carbon layer is 0.50 GPa, and the second indentation hardness of the metal layer is 0.40 GPa. That is, the condition that both the first indentation hardness of the carbon layer and the second indentation hardness of the metal layer are 0.20 GPa or more is satisfied. However, the condition that both the first indentation hardness of the carbon layer and the second indentation hardness of the metal layer are 0.15 GPa or less is not satisfied. In Comparative Example 2, the LC yield rate was 66%, and the ESR change rate was 1.3 times.
[0091] In the first embodiment (Examples 1, 3, and 5 in FIG. 7) and the second embodiment (Examples 2, 4, and 6 in FIG. 7), the adhesion between the carbon layer and the metal layer was improved, and the ESR change during the high-temperature load test was suppressed. In addition, a soft layer is present in which the first indentation hardness of the carbon layer or the second indentation hardness of the metal layer is 0.15 GPa or less. Therefore, the stress during the sealing process is mitigated, damage to the dielectric film is reduced, and the leakage current (LC) can be reduced.
[0092] In this way, when one of the first indentation hardness of the carbon layer and the second indentation hardness of the metal layer is 0.15 GPa or less and the other is 0.20 GPa or more, both the LC yield rate and the ESR change rate are improved.
[0093] As described above, the bonding strength between the carbon layer and the metal layer can be improved. That is, a highly reliable solid electrolytic capacitor can be provided. In addition, in the configuration of this embodiment, since there is no need to use an intermediate layer for improving the adhesion between the carbon layer and the metal layer, an increase in the thickness of the solid electrolytic capacitor is suppressed, and the volumetric efficiency is improved.
[0094] In the above-described configuration, one of the first indentation hardness of the carbon layer 114 and the second indentation hardness of the metal layer 115 is 0.15 GPa or less, and the other is 0.20 GPa or more. However, one of the first indentation hardness of the carbon layer 114 and the second indentation hardness of the metal layer 115 may be 0.10 GPa or less, and the other may be 0.30 GPa or more.
[0095] Although the above-mentioned solid electrolytic capacitor has a structure having end electrodes, the present invention can also be applied to a solid electrolytic capacitor structure having a lead frame.
[0096] Furthermore, the configurations and various derivative examples shown in the above-described embodiments can be combined as appropriate, and effects according to each combination can be achieved. [Explanation of symbols]
[0097] BD…Boundary surface F1…Front page F2…Second side F3…Side 3 F4…Fourth side F5…Side 5 F6…Side 6 1,1A...Solid electrolytic capacitor 10...Capacitor assembly 11...Capacitor element 19...Conductive material 20…First external electrode 30…Second external electrode 40...Insulating resin body 50...Conductive adhesive 111...Electrode foil 111F…electrode layer 111L…Porous layer 112...Dielectric layer 113...Solid electrolyte layer 114, 114A…Carbon layer 115,115A…Metal layer 400...Sealing body 401…Ceiling 402…Bottom 403...Side 1 404…Second side 1141…Carbon layer 1151...Metal layer
Claims
1. a capacitor element comprising: a flat membrane-like main body including a valve metal and having a porous layer with a plurality of holes on a surface of the valve metal; a dielectric layer formed on a cathode formation region; and a solid electrolyte layer formed on the dielectric layer, the capacitor element comprising: an anode terminal region in which the solid electrolyte layer is not formed on the main body; the cathode formation region in which the solid electrolyte layer is formed; a carbon layer formed so as to cover the solid electrolyte layer formed in the cathode formation region; and a metal layer formed so as to cover the carbon layer; a sealing body that seals a laminate in which a plurality of the capacitor elements are laminated with an insulating resin; a first external electrode connected to an end of the anode terminal region; a second external electrode connected to the cathode forming region; Equipped with When a first indentation hardness of the carbon layer and a second indentation hardness of the metal layer are measured by a nanoindentation method, One of the first indentation hardness and the second indentation hardness is 0.15 GPa or less, and the other is 0.20 GPa or more. Solid electrolytic capacitor.
2. The first indentation hardness of the carbon layer and the second indentation hardness of the metal layer are 2. The solid electrolytic capacitor according to claim 1, wherein one of the two is 0.10 GPa or less and the other is 0.30 GPa or more.
3. The carbon layer and the metal layer are One of the resins contains a thermosetting resin and the other contains a thermoplastic resin. The solid electrolytic capacitor according to claim 1 or 2.
4. 3. The solid electrolytic capacitor according to claim 1, wherein the carbon layer contains a thermosetting resin.
5. 3. The solid electrolytic capacitor according to claim 1, wherein the metal layer comprises a thermoplastic resin.
6. 3. The solid electrolytic capacitor according to claim 1, wherein the carbon layer contains a thermosetting resin, and the metal layer contains a thermoplastic resin.
Citation Information
Patent Citations
Solid electrolytic capacitor
JP2005086125A